Development of 16S rRNA-based probes for the Coriobacterium group and the Atopobium cluster and their application for enumeration of Coriobacteriaceae in human feces from volunteers of different age groups - Harmsen, H J; Wildeboer-Veloo, A C; Grijpstra, J; Knol, J; Degener, J E; Welling, G W (Applied and environmental microbiology, 2000)
Two 16S rRNA-targeted probes were developed: one for the Coriobacterium group and the other for the Atopobium cluster (which comprises most of the Coriobacteriaceae species, including the Coriobacterium group). The new probes were based on sequences of three new Coriobacteriaceae strains isolated from human feces and clinical material and sequences from databases. Application of the probes to fecal samples showed that formula-fed infants had higher numbers of Coriobacterium group cells in their feces than breast-fed infants. In addition, based on the presented results, it is hypothesized that with the increasing age of a person, the diversity of Atopobium cluster species present in the feces increases.